2022
DOI: 10.1177/13591053221107745
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline in mid-life: Changes in memory and cognition related to hypothyroidism

Abstract: This study assessed specific cognitive impairments within a primarily female, hypothyroid population, while controlling for factors that commonly contribute to cognitive decline. Participants ( N = 739) included 461 individuals with hypothyroidism. This study involved an online survey assessing several aspects of memory and cognition. Those with hypothyroidism generally scored worse on self-assessments of memory, higher perceived stress, high rates of depression and anxiety, greater fatigue, poorer concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, it is unclear why hippocampal neurons are affected in hypothyroidism. A large-scale study [ 77 ] showed that patients with hypothyroidism had a higher risk of memory impairment and also had a more than three-fold increase in the dementia risk. Several studies have reported an association between thyroid disorders and AD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is unclear why hippocampal neurons are affected in hypothyroidism. A large-scale study [ 77 ] showed that patients with hypothyroidism had a higher risk of memory impairment and also had a more than three-fold increase in the dementia risk. Several studies have reported an association between thyroid disorders and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed contributors include intermittent or chronic cerebral hypoperfusion, polypharmacy, cachexia, and protein energy undernutrition due to HF (Ampadu and Morley, 2015;van Nieuwkerk et al, 2023). Memory is a fundamental cognitive process that is crucial for the well-being and survival of HF patients (Faulkner et al, 2022;Stern et al, 2023). However, memory deficits are common and significantly hinder effective self-care management in patients with HF (Toledo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the thyroid gland in the proper function of the adult brain becomes even more evident with significant epidemiological data showing that hypothyroidism frequently coexists with depression or dementia and the positive effect of thyroid hormone supplementation in patients with drug-resistant depression [ 6 , 7 ]. A large-scale study showed that individuals with hypothyroidism faced a higher risk of memory impairment (up to 81%), higher perceived stress, more than a 3-fold increase in dementia risk, higher rates of depression and anxiety, greater fatigue, poorer concentration, and less motivation [ 8 ]. Some rare cases of autoimmune thyroiditis could lead to Hashimoto’s encephalopathy, presented by nonspecific clinical manifestations rapidly leading to progressive dementia, reversed by corticosteroid therapy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%